Encouraging interaction by applying cooperative learning (2001)
A project was conducted in order to improve oral interaction in English by applying cooperative learning to students of seventh grade. These students have lower levels of oral production and attend Marco Fidel Suárez public school. So, I decided to choose topics related to real life and to plan a series of activities of sensitization to create stable work groups and to increase oral interaction. According to the analysis and results, I can say that cooperative work and the oral activities help the students increase oral production, express better and use a foreign language with more security. In spite of the results, I consider that cooperative learning needs more time so that it can be successful. Students must have the will to cooperate. Only when students have that good will and can work together is the potential of acquisition of knowledge maximized.